2011
DOI: 10.1590/s0102-09352011000500024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain maturity stage on the quality of sorghum BRS-610 silages

Abstract: The quality of sorghum BRS-610 silages in seven stages of grain maturity, between the milky and dry stage, for determination of the ideal moment of ensilage was evaluated. The silos were open after 56 days of fermentation. The values for dry matter of silages increased from 199 to 473g/kg or from 19.9 to 47.3%, with the advance of stage maturity of grains. As for the quality of fermentation, the silages may be classified as excellent quality in every stage of maturity. The lower values of neutral detergent fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…A similar result was shown by Zhao et al ., 28 such that silage made from the late growth stage of Napier grass showed a higher NH 3 ‐N content than that in the early growth stage. It has been reported that the activity of plant proteases becomes greater at a more mature stage of forage 33 . Thus, in the present study, a high activity of plant proteases in DS may be responsible for the high NH 3 ‐N content of silages made from irradiated DS.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A similar result was shown by Zhao et al ., 28 such that silage made from the late growth stage of Napier grass showed a higher NH 3 ‐N content than that in the early growth stage. It has been reported that the activity of plant proteases becomes greater at a more mature stage of forage 33 . Thus, in the present study, a high activity of plant proteases in DS may be responsible for the high NH 3 ‐N content of silages made from irradiated DS.…”
Section: Discussionsupporting
confidence: 52%
“…The presence of NH 3 ‐N reflects the degradation of protein caused by plant enzymes, clostridia or other proteolytic microbes 33 . Compared to the epiphytic microbiota of DS, the epiphytic microbiota of FS caused a higher NH 3 ‐N content in FF and FD and Fig.…”
Section: Discussionmentioning
confidence: 97%
“…------Phase I (0 to 8 days)-------------Phase II (9 to 20days)------------Phase III (21 to 30days)----- silage mass compared to other acids, improves the anaerobic stability phase of ensiling process, helping on control of spoilage bacteria, since pH lowering favors the faster change of bacteria profile, reducing proteolysis, protein deamination, promoting the best use of soluble carbohydrates and resulting in an increased retention of silage nutrients (PODKÓWKA & PODKÓWKA, 2011). Butyric acid levels reported in silages corroborated those found by FARIA JÚNIOR et al (2011), which reported values between 0.2% to 2.5%, values indicative of good fermentation and preservation of silage since population of Costridium spp., largest producer of acid in question, probably had its growth inhibited due to pH lowering, ensuring better quality of silage. Regarding acetic and propionic acids, these remained at intermediate levels between the lactic and butyric acids, values that agreed with FRANÇA et al (2011) study, that used different sorghum hybrids as silage.…”
Section: Ingredientssupporting
confidence: 59%
“…The NH 3 ‐N content of all silages was lower than 100 g kg −1 TN, indicating that protein was not vigorously degraded by plant enzymes, clostridia or other proteolytic micro‐organisms during ensiling (Faria Júnior et al, 2011). Regardless of microbial factors, silage made from HS (H‐H and M‐H) presented higher NH 3 ‐N content than that from MS, which was inconsistent with the result of Zhao, Yin, Wang, et al (2021) that high NH 3 ‐N was exhibited at the advanced growth stage.…”
Section: Discussionmentioning
confidence: 99%